Religious Authority Fragmentation on Social Media: Da'wah Communication among Digital Ustadz and Religious Influencers - ahmad sofian; hasrat efendi samosir; zhila jannati; MUHAMMAD RANDICHA HAMANDIA (Yayasan Darussalam Bengkulu, 2026)
The rapid development of social media has fundamentally transformed da'wah communication and reshaped the structure of religious authority in contemporary Muslim societies. Digital platforms enable individuals to produce, distribute, and consume Islamic messages without relying solely on traditional scholars or religious institutions. This transformation has given rise to new religious actors, including digital preachers and religious influencers, whose legitimacy is increasingly constructed through popularity, audience engagement, and algorithmic visibility. Consequently, religious authority has become fragmented as scholarly legitimacy is gradually replaced by digital popularity. This study aims to analyze the fragmentation of religious authority on social media from the perspective of da'wah communication and to reconstruct a prophetic-based model of digital religious authority. This research employs a qualitative library research approach by examining scholarly publications related to digital da'wah communication, prophetic communication, religious authority, social media, platform algorithms, and religious influencers. Data were analyzed using the interactive analysis model of Miles, Huberman, and Saldaña through data collection, reduction, display, and conclusion drawing. The findings reveal that social media has transformed the mechanism of religious legitimacy through algorithmic logic, digital popularity, and audience participation, creating increasingly fragmented religious authority. Simultaneously, prophetic communication provides a normative framework based on humanization, liberation, and transcendence to reconstruct ethical and credible digital da'wah authority. This study proposes a conceptual novelty called the Prophetic Digital Religious Authority Model (PDRAM), positioning prophetic communication as the ethical foundation for developing adaptive, credible, and socially responsible digital religious authority. Keywords: Da'wah communication; Prophetic communication; Religious authority; Religious influencer Social media..